The Association Between Body Mass Index and Carpal Tunnel Syndrome Among Medical Students of Universitas Pelita Harapan: A Cross-Sectional Study - Riona Sutanto; Vivien Puspitasari; Astra Dea Simanungkalit; Pricilla Yani Gunawan (Lumina : Indonesian Journal of Neurology, 2026)
Introduction: Carpal Tunnel Syndrome (CTS) is one of the most common entrapment neuropathies, though its exact cause remains unclear.  Obesity has been identified as a potential risk factor, but previous studies have reported inconsistent findings.  This study aimed to analyze the association between Body Mass Index (BMI) and CTS among pre-clinical medical students at Universitas Pelita Harapan. Methods: This cross-sectional study utilized the Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) to assess symptom severity and functional status.  Body weight and height were self-reported via questionnaire to calculate BMI. Bivariate analyses are used to examine the association statistically, followed by stratified analyses to assess potential confounding factors. Results: A total of 201 participants met the inclusion and exclusion criteria for this study. Among them, 7.5% of the subjects presented with symptoms of CTS, and 5.0% experienced functional impairment. The association between BMI and CTS based on the severity of symptoms and functional status impairment was found to be significant (p = 0.004 and 0.049, respectively). Conclusion: Higher BMI was significantly associated with an increased likelihood of CTS symptoms and functional impairment. Gender and a history of diabetes mellitus were identified as potential confounding factors. Keywords: Carpal Tunnel Syndrome, Body Mass Index, Obesity